Tourism And Political Boundaries Border Markets As Tourist Attractions. - Mat Som,, Ahmad Puad; Mohamed, Badaruddin; Wong, Kong-Yew (2005)
Tourism appears to be an increasingly important industry in many border areas because many tourist destinations exist across boundaries.